Из Именного указателя к «Записным книжкам» Ахматовой [From An Index to Anna Akhmatova’s “Notebooks”] - Timenchik, Roman (Slavica Revalensia, 2018)
This article is the 33 installment in the series of annotations to Anna Akhmatova’s Notebooks. This particular installment concerns the following persons mentioned in Akhmatova’s notes: Vladimir Bonch-Bruevich (1873—1955), Ivan Bunin (1870—1953), Nadezhda Gedeonova (1898—1973), Anna Gorenko (i. e. the future Anna Akhmatova herself, 1889—1966), Aleksei Kruchenykh (1886—1968), Olga Kutasova (1929—2013), Viacheslav Losev (1890—1942), Vítězslav Nezval (1900—1958), Pavel Radimov (1887—1967), Elizaveta Tarakhovskaia (née Parnokh, 1895—1968), and Iakov Cherniak (1898—1955).